A Comparative Study on Crystal Structure and Magnetic Properties of Fe-Mn-Si and Fe-Mn-Si-Cr Alloys - Balo, S. Nevin (Springer, 2013)
In this study, the crystal structure and magnetic properties of Fe-30Mn-6Si (wt.%) and Fe-30Mn-6Si-5Cr (wt.%) alloys were compared by using X-Ray Diffraction (XRD) and Physical Properties Measurement System (PPMS) measurements. Detailed analysis of diffractograms at room temperature demonstrates that the Cr-free sample contains austenite and martensite phases, but for Cr-added sample the martensite phase disappears. According to micro hardness measurements, the presence of chromium decreased the hardness of the alloy. The magnetic saturation values at room temperature were measured as 11.32 emu/g for Fe-30Mn-6Si (wt.%) alloy and 18.34 emu/g for Fe-30Mn-6Si-5Cr (wt.%) alloy. The addition of Cr increased the magnetic saturation value of FeMnSi alloy while for both systems the hysteresis loop was quite narrow. As a result, both alloys exhibited soft magnetic characteristic.
3rd International Conference on Superconductivity and Magnetism (ICSM) -- APR 29-MAY 04, 2012 -- Istanbul, TURKEY
Keywords: FeMnSi and FeMnSiMn alloy; Shape memory properties; Soft magnetic characteristic